THE RESPONSIBILITIES OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN IMPLANTING ISLAMIC VALUES FOR STUDENTS - Misranik Misranik (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
This study aims to determine the Islamic and the responsibility of Islamic religious education teachers in instilling Islamic values in students. This research uses a descriptive qualitative approach. In obtaining data researchers used interview, observation, and documentation methods. The results of this study concluded that: 1) The forms of Islamic values that are applied, the value of faith, the value of worship, and the value of morals. 2) Supporting factors for Islamic Religious Education teachers in instilling Islamic values in students, namely, the existence of a community in a very religious school environment, besides that it has full support from the principal and school committee, an appropriate school vision and mission, and existence Mentoring. 3) PAI teachers have carried out their duties and obligations as well as their responsibilities as PAI teachers to instill Islamic values in students, and all comply with the existing curriculum in schools, and Islamic religious education teachers in instilling Islamic values in students with habituation. 4) The results of Islamic activities, it can be seen that all students wear a headscarf for those who are Muslim, their behavior and behavior are also good, as well as many Islamic achievements achieved.